ANALYSIS ON THE ROLE OF ENGINE COOLANT TEMPERATURE SENSOR IN GASOLINE ENGINE - Toto Sugiarto; Dwi Sudarno Putra; Wawan Purwanto (Universitas Sultan Ageng Tirtayasa, 2017)
A gasoline motor engine using electronic control system has several sensors and actuators driven by a computer. This paper aims to reveal the role of an engine temperature sensor mounted on a gasoline engine motor. The testing data shows that there is a connectivity between the temperature data obtained from the coolant temperature sensor with the fuel injection time and the exhaust gas emission content.